Impaired Cognitive Function and Altered Hippocampal Synaptic Plasticity in Mice Lacking Dermatan Sulfotransferase Chst14/D4st1 - Li, Qifa; Wu, Xuefei; Na, Xueyan; Ge, Biying; Wu, Qiong; Guo, Xuewen; Ntim, Michael; Zhang, Yue; Sun, Yiping; Yang, Jinyi; Xiao, Zhicheng; Zhao, Jie; et al. (Frontiers in Molecular Neuroscience, 2019)
Chondroitin sulfate (CS) and dermatan sulfate (DS) proteoglycans are major extracellular matrix (ECM) components of the central nervous system (CNS). A large body of evidence has shown that CS/DS proteoglycans (CSPG/DSPG) play critical roles in neuronal growth, axon guidance, and plasticity in the developing and mature CNS. It has been proposed that these proteoglycans exert their function through specific interaction of CS/DS chains with its binding partners in a manner that depends on the sulfation patterns of CS/DS. However, dermatan 4-O-sulfotransferase-1 (Chst14/D4st1) specific for DS, but not chondroitin 4-O-sulfotransferase-1 (Chst11/C4st1) specific for CS, regulates proliferation and neurogenesis of neural stem cell (NSCs), indicating that CS and DS play distinct roles in the self-renewal and differentiation of NSCs. It remains unknown whether specific sulfation profiles of DS has any effect on CNS plasticity. In the present study, Chst14/D4st1-deficient (Chst14-/-) mice was employed to investigate the involvement of DS in synaptic plasticity. First, behavior study using Morris Water Maze (MWM) showed that the spatial learning and memory of Chst14-/- mice was impaired when compared to their wild type (WT) littermates. In consistence with the behavior result, long-term potentiation (LTP) at the hippocampal CA3-CA1 connection was reduced in Chst14-/- mice compared to the WT mice. Finally, the protein levels of N-Methyl-D-aspartate (NMDA) receptor, α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor, postsynaptic density 95 (PSD95) and growth associated protein 43 (GAP-43) which are important in synaptic plasticity were examined and Chst14/D4st1 deficiency was shown to greatly reduce the amount of these proteins in the hippocampus. Together, this study indicates that specific sulfation of DS may facilitates synaptic plasticity in the hippocampus and play a role in learning and memory, which might be associated with the expression of glutamate receptors and other synaptic proteins.